Winter thunderstorms in Poland (1951–2020) - Wyrwas Jakub; Bielec-Bąkowska Zuzanna (Environmental & Socio-economic Studies)
One of the climate changes observed in mid-latitudes is the increase in the frequency of winter thunderstorms. These changes are also observed in Poland. For this reason, this study presents changes in the occurrence of thunderstorms in the cold half of the year and in winter in Poland from 1951 to 2020. The synoptic and thermodynamic conditions in the atmosphere, accompanied by particularly strong thunderstorms at this time of year, were also analysed based on selected cases of winter thun derstorms. The research was carried out on the basis of data from 46 synoptic stations, and the basic indicator was a day with a thunderstorm. Additionally, three cases of dangerous winter thunderstorms that occurred in Poland in the 21st century were analysed. For this purpose, synoptic maps, data from ERA5 reanalyses, aerological data and reports from the European Severe Weather Database were analysed. On this basis, it was found that there was a clear spatial differentiation of thunderstorms occurring in the cold half of the year, which in some regions of the country accounted for even more than 8% of all cases in the year. Although these thunderstorms are extremely rare, there are signs of an increase in their frequency during the studyperiod. The strongest influence on the occurrence of these phenomena in the cold season is air circulation and local conditions. Most of the thunderstorms considered were associated with atmospheric fronts. The strongest of them occurred during the passage of dynamic cold fronts, which are characterized by low potential energy and high wind shear values.